"Natural" Disasters, Cultural Framings, and Resilience in Indonesia: Transdisciplinary Engagements in an Immersion Program. Issue 2 (22nd April 2021) - Fraser, Jennifer; Hubbard, Karla
In this paper, we will discuss a two-week experiential learning trip to Indonesia, ranging from the design phase to a module course and in-country implementation with two institutional partners in country. The trip involved four faculty and eight students from disciplines ranging from Geology, Anthropology, Environmental Studies to Chemistry and Music. Comparison was at the heart of the project. Our team explored the cultural and functional responses to the 2004 tsunami in Banda Aceh and volcanic eruptions of Mount Merapi in Central Java. Contrasting views of cause and recovery proved especially enlightening. Acehnese responses were tightly woven with immediate pre-tsunami political upheaval along with Islamic framings of the disaster. In comparison, we found responses to volcanic eruptions on Java were quite different because the community affected was more multicultural. We will pepper our account of this pedagogical experience with personal outcomes, cultural interactions, and the trip's engagement with moving beyond interdisciplinarity to collaborative, transdisciplinary engagement.